2023
DOI: 10.1007/s40477-023-00783-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, barriers, and associated factors of obstetric ultrasound among pregnant women in public hospitals, Ethiopia, 2022: a cross-sectional study

Abstract: Background Obstetric ultrasound is a non-invasive imaging modality that uses sound waves to provide a real-time image of the foetus. Women’s knowledge of and attitudes toward ultrasound are suggested to influence their responses, and a variety of barriers also influence their practices. Objectives This study aimed to assess the knowledge, attitude, barriers, and associated factors of obstetric ultrasound among pregnant women in public hospitals in Addis Ababa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Also, housewives, government employees, and private employees were more likely to had good knowledge than students, merchants, and farmers. This finding was consistent with a study conducted in Ethiopia, which found that government employees were significantly associated with knowledge [21]. Furthermore, this finding was confirmed by a study conducted in Jeddah, where employment was found to be associated with good ultrasonography knowledge as a result of having more opportunities to obtain information and share experiences with others [5,9].…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…Also, housewives, government employees, and private employees were more likely to had good knowledge than students, merchants, and farmers. This finding was consistent with a study conducted in Ethiopia, which found that government employees were significantly associated with knowledge [21]. Furthermore, this finding was confirmed by a study conducted in Jeddah, where employment was found to be associated with good ultrasonography knowledge as a result of having more opportunities to obtain information and share experiences with others [5,9].…”
Section: Plos Onesupporting
confidence: 90%
“…However, it was much lower than a study done in Jeddah [9,16]. Whereas the magnitude of attitude of this study was lower than studies done in Jeddah and Ethiopia [9,20,21]. The discrepancies in the magnitude of knowledge and attitude of pregnant women towards obstetric ultrasound might be ascribed to differences in the study population, tools used to measure the outcome variables across the studies, and the sample size used.…”
Section: Discussioncontrasting
confidence: 73%